2018
DOI: 10.1097/brs.0000000000002679
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Incidence Is Associated With Sacral Curvature, Sacroiliac Joint Angulation, and Sacral Ala Width

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…In addition to the “line method” and the “angle summation method” we used in this study, several other methods are available to measure sacral curvature, as reviewed by Abola, Teplensky, Cooperman, Bauer, and Liu (2018). These include the S1–S4 sagittal Cobb angle, the angle formed by a bisecting line of S1 and a line from the inferior borders of S2 and S4, and the sacral table angle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the “line method” and the “angle summation method” we used in this study, several other methods are available to measure sacral curvature, as reviewed by Abola, Teplensky, Cooperman, Bauer, and Liu (2018). These include the S1–S4 sagittal Cobb angle, the angle formed by a bisecting line of S1 and a line from the inferior borders of S2 and S4, and the sacral table angle.…”
Section: Discussionmentioning
confidence: 99%
“…These include the S1–S4 sagittal Cobb angle, the angle formed by a bisecting line of S1 and a line from the inferior borders of S2 and S4, and the sacral table angle. On dry sacrums, Abola et al (2018) evaluated curvature by measuring the difference between the direct distance (using calipers) and the curved bony distance (using a tape measure laid flush with the ventral sacrum) from the sacral promontory to the inferior aspect of S4. Using the “line method,” Abitbol (1989) observed in 113 adult dry sacrums that 8.8% were angular, with S1‐S3 segments forming a right angle with S4–S5; 9.7% were flat with only part of S5 making an abrupt ventral angle; and the other 81.4% displayed a 29°–107° (mean of 65°) sacral curvature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a parameter of the sagittal spine pro le, pelvic incidence describes the angulation of the sacrum in the pelvis in relation to the hip joints, and in uences force transmission thus has been associated with spondylolisthesis. Abola et al 10 measured 120 cadaveric samples and found that a more curved sacrum, decreased sacral-ala width, and a more linear SI joint were related to an increased pelvic incidence.…”
Section: Discussionmentioning
confidence: 99%
“…05). This may be related to the difference in the pelvic bone structure between sexes (Schlösser et al, 2014;Giacomini et al, 2015;Bao et al, 2018), a larger anteroposterior diameter of pelvic inlet and wider pubic arch in female, and a higher degree of sacral anteversion in male (Abola et al, 2018).…”
Section: Comparison Of Spinal-pelvic Parameters and Pelvic Anatomicalmentioning
confidence: 99%